Finding the ideal automotive battery concept - Reiter, Christoph; Lin, Xue; Schlereth, Lars-Eric; Lienkamp, Markus (Forschung im Ingenieurwesen, 2019)
There are many degrees of freedom in the design of a battery concept for electric vehicles. A suitable lithium-ion battery (LIB) must be selected from different cell chemistries, types and sizes. During operation, the LIBs must always be kept in the optimum temperature range, thus a suitable battery thermal management system (BTMS) architecture must be developed. All these decisions have a direct impact on the later characteristics of the battery system and are subject to complex interactions. Therefore, the question arises of an automated method that supports the user in finding the ideal overall battery concept for a given vehicle concept. This paper introduces and discusses such a process. After an analysis of all relevant electrical and thermal influences and previous work on this topic, an approach is derived that allows automatic cell selection, modularization and BTMS development considering all relevant influences up to the vehicle level. The approach considers the electrical and thermal behavior on both the cell and the system level. Furthermore, the BTMS is simulated using a novel approach allowing the configuration of air and liquid cooling with any desired configuration. The complete simulation framework is made available under an open-source license.